2020
DOI: 10.1098/rsob.200088
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of non-coding regulatory elements to cardiovascular disease

Abstract: Cardiovascular disease collectively accounts for a quarter of deaths worldwide. Genome-wide association studies across a range of cardiovascular traits and pathologies have highlighted the prevalence of common non-coding genetic variants within candidate loci. Here, we review genetic, epigenomic and molecular approaches to investigate the contribution of non-coding regulatory elements in cardiovascular biology. We then discuss recent insights on the emerging role of non-coding variation in predisposition to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 148 publications
0
16
0
Order By: Relevance
“…Indeed, although genes involved in many biological pathways such as vascular tone and remodelling, lipid metabolism and inflammation have been identified, the precise molecular mechanism is still unknown 182,183 . Coronary artery diseases and myocardial infarction were the first diseases targeted in GWAS studies 184 . A study by Huang revealed the association between 3′‐UTR mutations of MEF2A and coronary artery diseases.…”
Section: Non‐coding Variants In Coronary Artery Diseases and Strokesmentioning
confidence: 99%
“…Indeed, although genes involved in many biological pathways such as vascular tone and remodelling, lipid metabolism and inflammation have been identified, the precise molecular mechanism is still unknown 182,183 . Coronary artery diseases and myocardial infarction were the first diseases targeted in GWAS studies 184 . A study by Huang revealed the association between 3′‐UTR mutations of MEF2A and coronary artery diseases.…”
Section: Non‐coding Variants In Coronary Artery Diseases and Strokesmentioning
confidence: 99%
“…19,20 or deep intronic regions. 21 Our understanding of the consequences of these types of variants and the non-coding genome organization in general is more limited than for exonic variants, but it is steadily expanding for example by continued mapping and functional characterization of regulatory elements, 22,23 expanded analysis of regulatory variants, [24][25][26] and improvements to prediction tools to aid in their interpretation are under development. [27][28][29]…”
Section: Initial Attempts For Prenatal Utilization Of Whole Genome Se...mentioning
confidence: 99%
“…Coronary Artery Disease (CAD) is a type of cardio-vascular disease associated with thickening of arterial walls and is a major cause of disease in developed countries (Malakar et al, 2019). Recent GWAS of CAD has shown a significant portion of associated SNPs to lie in non-coding regions of the DNA (Selvarajan et al, 2021;Villar et al, 2020). Using L-Hi-C-Reg we mapped a total of 193 SNPs (141 GWAS and 52 in LD) of total 409 SNPs to 1036 genes across the 55 cell lines with a total of 1737 interactions (Figure 6A, Table 1).…”
Section: Identifying Downstream Pathways Impacted By Regulatory Variantsmentioning
confidence: 99%